2018
DOI: 10.1212/wnl.0000000000004860
|View full text |Cite
|
Sign up to set email alerts
|

Associations between [ 18 F]AV1451 tau PET and CSF measures of tau pathology in a clinical sample

Abstract: This study provides Class III evidence that, in a clinical sample of patients with a variety of suspected neurodegenerative diseases, both CSF p-tau and [F]AV1451 distinguish AD from non-AD conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 38 publications
10
111
1
1
Order By: Relevance
“…did not evaluate age of onset by APOE ε4 alleles, it is possible that APOE ε4 may increase overall risk of LBD, but not accelerate age of onset, although a mechanism for this association remains unclear. Their inclusion of NFTs within the occipital‐temporal gyrus, rhinal sulcus, and entorhinal region (ie, Braak Stage III) in their sample may have influenced findings as APOE ε4 has been associated with tau deposition and distribution . Thus, it is possible that their findings were associated with tau versus Lewy pathology.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…did not evaluate age of onset by APOE ε4 alleles, it is possible that APOE ε4 may increase overall risk of LBD, but not accelerate age of onset, although a mechanism for this association remains unclear. Their inclusion of NFTs within the occipital‐temporal gyrus, rhinal sulcus, and entorhinal region (ie, Braak Stage III) in their sample may have influenced findings as APOE ε4 has been associated with tau deposition and distribution . Thus, it is possible that their findings were associated with tau versus Lewy pathology.…”
Section: Discussionmentioning
confidence: 96%
“…20 In contrast, APOE 4 did not appear to hasten onset in the pure LBD group, despite previous research suggesting APOE 4 increases risk of dementia in autopsyconfirmed LBD. 21 In a study by Tsuang et al, 21 22 Thus, it is possible that their findings were associated with tau versus Lewy pathology. Additionally, few homozygous APOE 4 carriers in our LBD group, which is more associated with dementia risk, may have reduced power.…”
Section: Discussionmentioning
confidence: 99%
“…An initial study pointed toward better discriminative accuracy for [ 18 F]flortaucipir PET compared with CSF tau in mild-to-moderate AD, 35 while another found equivalent performance for discriminating AD from non-AD neurodegenerative disorders. 36 The superior performance of [ 18 F]flortaucipir compared with established MRI markers suggests that [ 18 F]flortaucipir could precede structural MRI when the differential diagnosis includes AD dementia. In case of a negative [ 18 F]flortaucipir scan, the atrophy pattern might help determine the type of non-AD dementia.…”
Section: Discussionmentioning
confidence: 99%
“…To measure tau pathology in vivo, we used CSF and PET measurements. Previous studies have demonstrated associations between CSF p-tau and tau-PET uptake in Alzheimer's disease-related brain regions [29][30][31]. The primary outcome measure of the study was tau pathology as measured by voxel-wise [ 18 F]MK6240 SUVR (TRIAD cohort), [ 18 F]Flortaucipir SUVR (ADNI tau-PET cohort), and CSF phosphorylated tau (ADNI CSF cohort).…”
Section: Statistical Analysesmentioning
confidence: 99%